Legal Protection for Mubaligh Muhammadiyah in Conveying Da'wah Through Social Media Perspective of Freedom of Opinion - Zainuddin Zainuddin; Ismail Koto. (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
This study aims to provide legal protection for Mubaligh Muhammadiyah who deliver Da'wah through social media from the perspective of freedom of opinion. In terms of conveying da'wah through social media, freedom of opinion is regulated under Act No. 19 of 2016 concerning Information and Electronic Transactions. and prevention efforts so that Muhaligh Muhammadiyah does not violate the law related to conveying da'wah from the perspective of freedom of opinion on social media. Legal protection and prevention efforts aim to convey da'wah quickly through social media and avoid violations of the law so that the da'wah of Amar Makruf Nahi Mungkar can be conveyed to the public. Norms, rules, and legal principles related to the purpose of this study, namely regarding legal protection for mubaligh Muhammadiyah in conveying da'wah through social media from the perspective of freedom of expression, will be a source of secondary data in this study, which has a type and is based on normative legal research, including primary legal materials, secondary, and tertiary, which will be collected, processed, and analyzed qualitatively with a statutory approach (statute approach). The intended normative study will be packaged in a scientific paper as the main output of this research in the form of articles that, God willing, will be published in the journal De Lega Lata: Journal of Legal Studies, indexed in Sinta 3 through OJS, http://jurnal.umsu.ac.id/index.php/delegalata/index in the publication period in accordance with the research schedule, and added with other outputs, namely the registration of intellectual.